Synthesis and Reactivity of Oligo(ethylene glycol)-Tethered Morita–Baylis–Hillman Dimers in the Formation of Macrocyclic Structures Showing Remarkable Cytotoxicity - Marco Paolino; Mario Saletti; Jacopo Venditti; Arianna Zacchei; Alessandro Donati; Claudia Bonechi; Germano Giuliani; Stefania Lamponi; Andrea Cappelli (Pharmaceuticals)
Background/Objectives: Crown ethers have received increasing interest owing to their ability to form stable complexes with cations. This molecular feature has been successfully exploited in the development of biologically relevant ionophores. Methods: In order to obtain innovative crown ethers derivatives, a Morita–Baylis–Hillman adduct (MBHA) acetate (4) bearing a phenylacetylene moiety was dimerized via the click-chemistry CuAAC reaction with oligo(ethylene glycol) diazide derivatives to build-up a small series of dimeric MBHA derivatives (5a-d). These dimeric MBHA derivatives were reacted with n-butylamine to afford tunable macrocyclic crown ether-paracyclophane hybrid architectures (6a-d). Results: Compounds (E,Z)-6a, (E,E)-6a, 6b-d showed, in human breast cancer MDA-MB-231 and human melanoma A375 cells, IC50 values comparable with those of reference anticancer agent Doxorubicin. Conclusions: This exploration approach provides original new macrocyclic architectures potentially useful as anticancer agents.